Radiological age estimation using third molars mineralization in a sample attending orthodontic clinics (A retrospective study) - Kadhom , Zainab M (Journal of Baghdad College of Dentistry, 2020)
Background: The evaluation of the chronological age is a practical method in crime investigation field that assists in identifying individuals to treat them as underage or adult. This study aimed to assess the stages of third molars mineralization in relation to chronological age of Iraqi individuals, determine the gender differences and arches (maxillary/mandibular) differences.Materials and Methods: A total of 300 orthopantomograms of orthodontic patients were collected according to specific criteria and evaluated visually. The developmental stages of maxillary and mandibular third molars were determined according to Demirjian method. The chronological age was recorded according to the particular mineralization stages at which it reached considering genders, sides and jaws. Comparisons were done using paired sample and independent sample t-tests.Results: Results showed that there was no statistically significant difference (P>0.05) between maxillary and mandibular third molars. The maxillary third molars reached earlier than mandibular one in stages F and G. There was no significant difference between the mean ages of males and females at each given developmental stage in the maxillary and mandibular third molars except for the stage D in the maxilla and stages D and E in the mandible. The development of third molar teeth on the right and left sides was similar except for the maxillary arch in males when there was a significant difference in stage C and D and stage E in the mandibular arch.Conclusion: The Demirjian method is an excellent approach for age assessment using Orthopantomogram. All of the differences between the current study and other studies could be because of the difference in the populations who were chosen from different geographical areas.Keywords: Age estimation, Demirjian method, third molar, Orthopantomogram, chronological age.